Gestão de portfólio de produtos/projetos e processo de desenvolvimento de produtos : diagnóstico em uma empresa de autopeças. - Schelp, Mathias Xavier (2007)
To choose the right projects, to develop them fast, achieving high quality patterns, and respecting the costs pressures. These are no questionable demands in the actual market conditions. The utilization of Product Development Processes and Portfolio Management are some of the main manners to achieve these goals. The Product Development Process adopted in a specific organization should be essentially aligned with the product-life-cycle. In addition, companies need to evaluate and make decisions on the products / projects based in an overall view provided by the Portfolio Management systematics and tools. This research focuses in these issues. The main objective is to analyze the integration between the Product Development Process and the Portfolio Management in a company from the automotive industry aimed at identifying the best practices and improving opportunities. The research methodology is the realization of a literature review followed by a case-study. The main result is the proposal of a Portfolio decision model, and the realization of a case-study based on this model proposal. The main contribution is to detail the Portfolio decisions, based in a PDP model, along the product-life-cycle.